576. Half-dose Valganciclovir Prophylaxis is Safe and Cost-effective in CMV Seropositive Renal Transplant Recipients. (31st December 2020) - shi, yiyun; Rogers, Ralph; Vieira, Kendra; Merhi, Basma; Osband, Adena; Bayliss, George; Gohh, Reginald; Morrissey, Paul; Farmakiotis, Dimitrios
Abstract: Background: Observational studies suggest that half-dose valganciclovir (VGV) prophylaxis (450 mg daily for normal renal function) is as effective as full-dose (900 mg daily) in preventing CMV infection among kidney transplant recipients (KTR). However, this practice is not supported by current guidelines, for fear of selecting resistance, mainly in high-risk, i.e. donor CMV seropositive/recipient negative (D+/R-) KTR. Full-dose VGV is costly, and possibly associated with higher incidence of neutropenia and BK viremia. Our institution adopted half-dose VGV prophylaxis for R+ KTR in January 2018. Methods: We included R+ KTR transplanted between 1/1/2014 and 12/31/2018 at our center. Data were censored at 1-year post-transplant, graft loss or death. Primary outcomes were early (< 6 months from transplant) and any CMV viremia. Secondary outcomes were neutropenia, BK viremia, graft loss and death. Categorical variables were compared with χ  2 or Fisher's exact tests, continuous variables with the Mann-Whitney test. We used log-rank and Gray's tests to compare cumulative incidence of outcomes, after adjustment by propensity score for differences in baseline characteristics. Results: 106 R+ KTR received full-dose and 35 half-dose VGV. Antithymocyte globulin (ATG) induction was associated with significantly higher cumulative incidence of both early (P=0.017) and any (P=0.02) CMV viremia, compared to basiliximab induction (Fig. 1). After adjusting for gender and induction regimen, we noted a signal for higher cumulative incidence of any (P=0.044), but not early (P=0.598) CMV viremia in the full-dose VGV group (Fig. 2). There were no significant differences (P >0.1) in incidence of neutropenia, BK viremia, graft loss or death between the two groups. Cost savings were estimated at $2630 per CMV R+ KTR (Table 1). Table 1. Comparison of outcomes and cost between the two anti-CMV prophylaxis groups. Data are presented as n (%), unless otherwise indicated. Fig 1. Probability of CMV viremia in KTR who received ATG vs. basiliximab induction. Fig 2. Probability of CMV viremia in KTR who received full-dose vs. half-dose VGV prophylaxis. Conclusion: In our pilot series, half-dose VGV was at least as effective as full-dose VGV in preventing CMV viremia in R+ RTR, and less costly. If larger scale studies verify generalizability of these results, half-dose VGV may be considered as standard of care for R+ KTR. In KTR, the antimetabolite probably contributes to neutropenia more than VGV prophylaxis. Disclosures: All Authors : No reported disclosures